Visual Language for Use Case Description. (8th December 2015) - de Souza, Alessandro J.; Cavalcanti, Anderson Luiz O.
Summary: Use cases have been widely adopted by software engineers to model user–system interaction. However, its fragmented and textual description of functionalities has been inadequate for user‐centered design concerns. This has led human–computer interaction professionals to create their own methods and techniques, which has often had the opposite philosophy from that used by software engineers when modeling user–system interactions. Therefore, the present paper proposes the Visual Language for Use Case Description aiming to improve the support of use cases for user‐centered design by projecting a common artifact for the communication between both the human–computer interaction and the software engineering communities. To obtain the perceptions of potential users about Visual Language for Use Cases Description, an experimental study involving software development students and professionals was conducted. Copyright © 2015 John Wiley & Sons, Ltd.